Faste forbindelser som genrekonstituenter: En undersøgelse i de danske visehåndskrifter før 1591 - Duncker, Dorthe (Danske Studier, 2024)
Prior to the first printed edition of Danish ballads from 1591 nine handwritten song books have been handed down, containing 1,014 records of ballads and lyrical poems. Though only one or a few versions of each handwritten song existed, the collectors seem to have been able to distinguish ballads from lyrical poems. This could be due to formulaic language, and the hypothesis tested in this article is that fixed expressions function as genre constituents. In a corpus of 526 versions of ballads and lyrical poems, representing half of the records from the nine oldest song books, fixed expressions are identified through corpus linguistic methods. It appears that a few genre significant formulas are distributed across the material and that these expressions tend to occur quite early in the texts (within the first 100 words) thereby rendering the text type identifiable. In 86 % of the texts, the question of genre is solved by hearing or reading the first occurrence of a genre significant expression.